Correlation between White Blood Cell Count and Myocardial Infarction Mortality in Patients admitted at Tertiary Care Center of Philippines - Paudel, Pratik; B. Lopez, Mariano; Gautam, Rakshya (Annapurna Journal of Health Sciences, 2023)
Introduction: Coronary artery disease (CAD) continues to be a major cause of morbidity and mortality in developed as well as developing countries. This study aims to find out the correlation between elevated WBC and AMI mortality and also to enhance as an independent marker for higher risk for in-hospital patients which would finally help for risk stratification and better care for such presentation. Methods: This is a retrospective research evaluating all adult patients with AMI who were admitted to Rizal Medical Center from January 1, 2016 to December 31, 2017. Clinical data were retrieved from the Medical Records Section and Department of Laboratory Medicine. Detailed history, physical examination and relevant investigations such as complete blood count and electrocardiographic results were reviewed. All data was managed by Microsoft Excel for windows and after collecting a sample size of 225 cases. Analysis was executed using SAS Software Version 9.3. Results: Relationship existed between clinical outcome and white blood cell count. The patients with elevated WBC on comparison to patients with normal WBC had 3 times more risk of dying (discharged(5.8%)/died(18.7%), p value 0.028. The mean WBC for favourable clinical outcome was 11.87±4.85 S.D which is lower as compared to the poor clinical outcome averaged 13.87±6.20 S.D. (p .028 < .05). Conclusion: The results indicate that patients with elevated white blood cell count would be more likely to have poor clinical outcome compared to patients who have normal white blood cell count. White blood cell count within 24 h of admission for an AMI is a strong and independent predictor of in-hospital mortality.